Inferential Procedures for Comparing the Accuracy and Intrinsic Measures of Multivariate Receiver Operating Characteristic (MROC) Curve - Vardhan, R. Vishnu; Sameera, G.; Chandrasekharan, P.A.; Beere, Thulasi (International Journal of Statistics in Medical Research, 2015)
A number of classification techniques are prevailing in literature. Of them, one of the most important techniques is the Receiver Operating Characteristic (ROC) curve. A multivariate extension of this technique is proposed in the recent years. This technique helps in classifying the objects/individuals into one of the two classes by considering two or more markers. The most important measure of an ROC curve is the Area Under the Curve (AUC) and it explains the accuracy and discriminating ability of the test under study. There are two intrinsic measures of ROC namely sensitivity (Sn) and specificity (Sp). Further, two ROC curves can be compared by comparing their measures. The practical application of the proposed inferential procedures is explained with the help of two real datasets namely, Indian Liver Patient (ILP) Dataset and Intra Uterine Growth Restricted Fetal Doppler Study (IUGRFDS) dataset. These inferential procedures are developed based on the measures of multivariate ROC (MROC) curve proposed by Sameera G, R Vishnu Vardhan and KVS Sarma [1].